Silibinin Suppresses Inflammatory Responses Induced by Exposure to Asian Sand Dust - Se-Jin Lee; So-Won Pak; Woong-Il Kim; Sin-Hyang Park; Young-Kwon Cho; Je-Won Ko; Tae-Won Kim; Joong-Sun Kim; Jong-Choon Kim; Je-Oh Lim; In-Sik Shin (MDPI AG, 2024)
Asian sand dust (ASD), generated from the deserts of China and Mongolia, affects Korea and Japan during spring and autumn, causing harmful effects on various bio-organs, including the respiratory system, due to its irritants such as fine dust, chemicals, and toxic materials. Here, we investigated the therapeutic effects of silibinin against ASD-induced airway inflammation using mouse macrophage-like cell line RAW264.7 and a murine model. ASD was intranasally administered to mice three times a week and silibinin was administered for 6 days by oral gavage. In ASD-stimulated RAW264.7 cells, silibinin treatment decreased tumor necrosis factor-α production and reduced the expression of p-p65NF-κB, p-p38, and cyclooxygenase (COX)-2, while increasing heme oxygenase (HO)-1 expression. In ASD-exposed mice, silibinin administration reduced inflammatory cell count and cytokines in bronchoalveolar lavage fluid and decreased inflammatory cell infiltration in lung tissue. Additionally, silibinin lowered oxidative stress, as evidenced by decreased 8-hydroxy-2'-deoxyguanosin (8-OHdG) expression and increased HO-1 expression. The expression of inflammatory-related proteins, including p-p65NF-κB, COX-2, and p-p38, was markedly reduced by silibinin administration. Overall, silibinin treatment reduced the expression of p-p65NF-κB, COX-2, and p-p38 in response to ASD exposure, while increasing HO-1 expression both in vitro and in vivo. These findings suggest that silibinin mitigates pulmonary inflammation caused by ASD exposure by reducing inflammatory signaling and oxidative stress, indicating its potential as a therapeutic agent for ASD-induced pulmonary inflammation.